PWE-124 Understanding The Mechanisms Underpinning Treatment Non-response In Primary Biliary Cirrhosis: A Tool For Treatment Stratification. (9th June 2014) - Pitts, AC; Palmer, JM; Jones, DE; Dyson, JK; Griffiths, L; Ducker, S; Kirby, JA
Abstract : Introduction: The pathogenesis of Primary Biliary Cirrhosis (PBC) is poorly understood. The Th1 CD4 + cell subset has known involvement, however, the Th17 subset demonstrated in autoimmune disease requires further investigation. Ursodeoxycholic acid (UDCA) is the primary treatment and response is measured by liver biochemistry change; suboptimal improvement (non-response) has a poorer prognosis and there remains a lack of effective second-line therapies. This study aimed to pilot transcriptional investigation of T-cells in PBC, including UDCA response stratification and Th17 polarisation, following recent revelation of demographic associations with non-response. Methods: Affymetrix® GeneChip® Microarray analysis examined the gene expression differences of CD4 + T-cells isolated from PBC responders (n = 3), non-responders (n = 4) and healthy controls (n = 3). The samples studied were taken at baseline and after culture with anti-CD3/28 beads +/- Th17 polarising cytokines. Results: 900 genes were significantly differentially expressed with >2 fold change in patients versus healthy controls and 113 genes in responsive versus non-responsive groups at baseline. Study of CD3/28 activated cells +/-Th17 polarisation revealed no significant differences. In PBC patients, features up-regulated included CD69 (adjusted p < 0.00005) and those down-regulated HLA class II transcripts (p < 0.05). Conclusion: Despite a small cohort, for the first time using microarray, this project demonstrated differences between PBC patients and healthy individuals and, importantly, between UDCA response groups. This substantiates the view that UDCA non-responsive disease represents a distinct biological entity requiring different clinical management. Up-regulation of the activation marker CD69 implies ongoing T-cell stimulation in PBC. HLA class II transcript down-regulation may imply a role in T cell anergy or regulation. Disclosure of Interest: None Declared.